Entrapment Between Narratives: The Millennial Voice and Degendering Organizational Resilience - Witmer, Hope (Frontiers in Sustainability, 2021)
The Covid-19 pandemic pushes organizations to innovate, adapt and be responsive to new conditions. These demands are exacerbated as organizations respond to the triple sustainability challenge of social and environmental issues alongside economic recovery. These combined factors highlight the need for an inclusive definition of organizational resilience, the increased agility to adapt, learn and transform to rapidly shifting external and internal conditions. This paper explores a gendered perspective of organizational resilience and the implications for degendering the concept to incorporate masculine and feminine constructs equally valuable to the theory and practices of organizational resilience during times of crisis. Viewing the organizational demands of crisis and the expectations of the millennial workforce through the degendering lens elucidates conceptualizations of gender constructions and power that limit inclusive practices and processes of organizational resilience. Data was used from focus groups of men and women between the ages of 21-35 (millennials) who have experience in the workplace and a shared knowledge of sustainability including social aspects of gender equity and inclusion. The Degendering Organizational Resilience model (DOR) was used for analysis to reveal barriers to inclusive, resilient organizational practices. The data was organized according to the the three aspects of the DOR, power structures, gendering practices and language. A unique contribution of this study is that it explores a cross-cultural gender perspective of organizational resilience focused on a specific cohort group, the millennials. Based on the findings three organizational recommendations for practice were identified. These include recommendations for policies and practices that deconstruct inequitable practices and co-create more agile structures, practices, and narratives for sustainable and resilient organizations.